Potential implications of a more timely living kidney donor evaluation. Issue 11 (17th April 2018) - Habbous, Steven; McArthur, Eric; Sarma, Sisira; Begen, Mehmet A.; Lam, Ngan N.; Manns, Braden; Lentine, Krista L.; Dipchand, Christine; Litchfield, Kenneth; McKenzie, Susan; Garg, Amit X.; ,
Abstract : Living donor kidney transplantation is the most promising way to avoid or minimize the amount of time a recipient spends on dialysis before transplantation. We studied 887 living kidney donors at 5 transplant centers in Ontario, Canada, who started their evaluation and donated between April 2006 and March 2014. Using a series of hypothetical scenarios, we estimated the impact of an earlier living donor evaluation completion and donation on the number pre‐emptive transplants, the time spent on dialysis, healthcare cost savings from averted dialysis costs (CAD 2016), and the number of additional transplants. During the study period, if the donor transplants occurred 3 months earlier, the healthcare system would save on average 12 055 (standard deviation [SD] 13 594) per recipient; 21 recipients could have avoided dialysis altogether, and 57 additional transplants (a 26% increase) could have occurred each year. For the 220 living kidney donor transplants performed in Ontario, Canada, each year, this translates to a total annual cost savings of 2.7M. In conclusion, a more timely evaluation of living donor candidates and their intended recipients may increase the supply of kidneys for transplantation. Improved evaluation efficiency may also yield more pre‐emptive transplants and substantial healthcare cost savings through averted dialysis costs. Abstract : An earlier and more efficient living donor candidate evaluation may enable more living donor transplants, improve recipient outcomes, and reduce healthcare costs.